Program Pelatihan Berbasis Kunjungan Rumah dalam Perawatan Jangka Panjang Anak Stunting Meningkatkan Persepsi, Self-Efficacy dan Kesiapan Kader Pembangunan Manusia - Rismawan, Made; Negara, I Gusti Ngurah Made Kusuma; Astawa, I Gede Satria; Muncan, I Gusti Agung Mas Widia Paramita; Wati, Ni Luh Gede Diana (Jurnal Gema Keperawatan, 2025)
Human Development Cadres have a strategic role in supporting the long-term care of stunted children in the community. However, suboptimal perceptions, self-efficacy, and readiness of cadres often become obstacles in carrying out the duties of human development cadres. This study aims to determine the effectiveness of a home visit-based training program on the perceptions, self-efficacy and readiness of Human Development Cadres in the long-term care of children with stunting. This study used a pre-experimental design with pretest-posttest one group only on 30 Human Development Cadres in the Puskesmas of Kintamani III (March-September 2024). The home visit-based training program included material on stunting, nutrition, health, and community empowerment. Perceptions, self-efficacy, and readiness of Human Development Cadres were measured before and after the intervention using instruments developed based on the detailed tasks of Human Development Cadres. Paired t-test was used to analyze the data. The results showed significant differences in perception, self-efficacy, and readiness (p0,001). The home visit-based training program has a significant effect on improving perceptions, self-efficacy and readiness of Human Development Cadres in the long-term care of children with stunting. The home visit-based training program needs to be part of routine interventions in empowering Human Development Cadres, especially to support the long-term care of children with stunting.